2021
DOI: 10.3390/antibiotics10020199
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Prescription Pattern in Ho Teaching Hospital, Ghana: Seasonal Determination Using a Point Prevalence Survey

Abstract: A standardised Global Point Prevalence Survey (PPS) tool was used to determine the antimicrobial prescription pattern in the Ho Teaching Hospital on two separate occasions in a total of 14 wards in the hospital, including dedicated wards for paediatrics and neonates. Manually collected and anonymised data were entered, validated, analysed and reported using a web-based global PPS application. With 147 and 153 patients considered in the July 2019 and January 2020 surveys, respectively, 98 patients (66.7%) and 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 15 publications
4
18
0
Order By: Relevance
“…In the study hospital, antibiotics are prescribed in both branded and generic forms, but mostly as generics, and they are in the EML and hospital formulary. Similar indications for antibiotic use have previously been identified in Ghana [ 6 , 9 , 22 , 23 ].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In the study hospital, antibiotics are prescribed in both branded and generic forms, but mostly as generics, and they are in the EML and hospital formulary. Similar indications for antibiotic use have previously been identified in Ghana [ 6 , 9 , 22 , 23 ].…”
Section: Discussionsupporting
confidence: 68%
“…This paper reports part of the activities and results of one of the partnerships of the University College London Hospital NHS foundation trust (UCLH) with the University of Health and Allied Sciences (UHAS) and Ho Teaching Hospital, which are both in the Ho municipality in the Volta region of Ghana. The activities carried out in this partnership included a periodic Global Point Prevalence Survey (GPPS) [ 9 ] to establish patterns of antimicrobial use and an AMR/AMS training and capacity-building workshop for healthcare professionals. The aim of this study was to assess the improvement in AMS knowledge after a training session and to build the capacity and skills of healthcare professionals in order to support the implementation of antimicrobial stewardship programmes in Ho Teaching Hospital in the Volta region of Ghana.…”
Section: Introductionmentioning
confidence: 99%
“…Point prevalence surveys of antibiotic use, when repeated regularly, provide data on patterns of antibiotic use and serve as a benchmark for antibiotic stewardship activities. Observations from previous multicentre PPS in Ghana, 14 , 16 , 24 including findings from this current study, suggest four major antibiotic prescribing indicators for antimicrobial stewardship (AMS) interventions. First, metronidazole, ceftriaxone, cefuroxime, and amoxicillin/clavulanic acid constitute good candidates for AMS because of their high frequency of prescription in Ghana.…”
Section: Discussionmentioning
confidence: 59%
“…This shows that rates of antibiotic use among inpatients in KBTH have been fairly consistent over the past two decades. Studies from other hospitals in Ghana showed comparatively higher prevalence rates with Komfo Anokye Teaching Hospital reporting a prevalence of 64% [ 27 ]; Ho Teaching Hospital recorded 66.7% [ 28 ], and Keta Municipal Hospital recorded 82.0% [ 29 ]. Prevalence from this study compared favourably with antimicrobial prevalence in Africa (63%) but is still relatively high compared to North America (34.0%), South Europe (31.7%) or East Europe (30.3%) [ 16 ].…”
Section: Discussionmentioning
confidence: 99%